2000
DOI: 10.1093/clinchem/46.9.1338
|View full text |Cite
|
Sign up to set email alerts
|

Lower Cardiac Troponin T and I Results in Heparin-Plasma Than in Serum

Abstract: Background: The use of plasma rather than serum for determination of cardiac troponins can improve turnaround time and potentially avoid incomplete serum separation that may produce falsely increased results. We investigated the influence of incomplete serum separation and the effect of heparin-plasma on cardiac troponin concentrations. Methods: Serum and heparin-plasma samples were drawn simultaneously from 100 patients (50 patients with acute coronary syndrome and 50 patients after open heart … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(23 citation statements)
references
References 9 publications
0
22
0
1
Order By: Relevance
“…Serum and plasma values are significantly correlated, but a tendency toward slightly lower serum concentrations has been documented in dogs, 54 whereas the opposite has been found in humans. 54,64 Separate reference intervals might, therefore, be needed. Troponin reportedly has long-term stability at À70 to À80°C, 8,65 but is not stable at room temperature, 54 refrigerator temperature, 60 or À20°C.…”
Section: Measurement Of Cardiac Troponinsmentioning
confidence: 99%
“…Serum and plasma values are significantly correlated, but a tendency toward slightly lower serum concentrations has been documented in dogs, 54 whereas the opposite has been found in humans. 54,64 Separate reference intervals might, therefore, be needed. Troponin reportedly has long-term stability at À70 to À80°C, 8,65 but is not stable at room temperature, 54 refrigerator temperature, 60 or À20°C.…”
Section: Measurement Of Cardiac Troponinsmentioning
confidence: 99%
“…The findings from one cTnI assay therefore cannot be extrapolated to another unless the assays have been calibrated and have comparable analytical performance at the same clinical decision levels 1 . A difference has also been reported 7,8 between serum and heparinised plasma in human clinical samples. The purpose of this paper is to report the findings of measurements of cTnI in normal horses from both serum and heparinised plasma analysed through a standard Australian commercial laboratory (Mayne Health Vetnostics).…”
mentioning
confidence: 99%
“…Two recently published studies showed a decrease in cTnT levels measured in plasma compared with serum samples 1,2 . One showed an average difference of 15% 1 and the other showed no difference on average, but an idiosyncratic relative difference of > 20% between samples in eight of 100 cases 2 . Both groups of authors concluded that cTnT samples should not be collected in heparinized tubes.…”
Section: Discussionmentioning
confidence: 97%
“…Hence, none of these results would have been considered as negative if one took 0.03 µg/L as the upper reference limit cut‐off for the test, given that the reproducibility of the test is 0.03 µg/L and no cTnT should normally be detected in the blood. Similarly, Stiegler et al 2 only included values > 0.05 µg/L in both tubes. All eight samples that showed a relative difference of > 20% in this study had concentrations of cTnT higher than 0.2 µg/L in both tubes and would have been treated as a positive result by a clinician managing the patient, regardless of the collection method.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation